Anti-inflammatory response of IL-4, IL-10 and TGF-β in patients with systemic inflammatory response syndrome - Donato Torre; Roberto Tambini; Silvana Aristodemo; Giovanna Gavazzeni; Antonio Goglio; Carla Cantamessa; Agostino Pugliese; Gilberto Biondi (Mediators of Inflammation)
The systemic inflammatory response syndrome (SIRS) is an inflammatory process seen in association with a large number of clinical infective and noninfective conditions.